The Role of Social Media/Internet During the Covid-19 Pandemic for Local Communities Around the University of Jember - Prastika, Andika; Eriska Eklezia Dwi Saputri (Jurnal Masyarakat Maritim, 2022)
A new variant of the coronavirus, namely SARS-CoV-2 which causes a disease, namely COVID-19, began to be reported in December 2019 in Wuhan, China. The virus spread almost all over the world and arrived in Indonesia for the first time in March 2020. COVID-19 then became a concern because it claimed many lives and spread the disease very easily, namely through human-to-human droplets. Several countries, including Indonesia, have finally implemented large-scale social restrictions (PSBB) in which these restrictions affect various sectors of society, both in terms of economy, education, society, and others. Advances in technology and information now make all activities feel more efficient, especially the problem of using social media. The development of this communication technology encourages communication actors who are not only used by individuals but become an alternative that is used to provide information and education related to the COVID-19 pandemic. This study wants to explore the education of the people of Jember Regency on COVID-19 through social media in it. Furthermore, this study also identifies how the media affects the local people of the University of Jember by involving social media communication in strategies to increase awareness about efforts to handle and prevent COVID-19. The implementation method used is qualitative. The required data is obtained from the distribution of online questionnaires Keywords: covid-19, education, information, social media